2005
DOI: 10.1007/s11137-005-0103-9
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Pd from Spent Fuel: 2. Sorption Recovery of Pd from Nitric Acid Solutions on Anion-Exchange Resins

Abstract: Recovery of Pd from nitric acid solutions on various anion-exchange resins is studied. The effects of the HNO 3 concentration, temperature, and aminoacetic acid on the desorption of Pd are examined. Results of the experiments on Pd recovery from actual solutions from spent fuel reprocessing are reported.The high yield of the Pt group metals in U fission allows NPP spent fuel to be considered as a promising source of Pd and Rh, which can be widely used in various areas of engineering [1,2].After nitric acid dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…The distribution of radionuclides between the solution and Pd precipitated from the desorbate formed in sorption recovery of palladium from true HLW [10] is presented in Table 4 as an example. The solution contained 690 mg l !1 Pd, 3 M HNO 3 and 0.1 M DTPA (the specific activity per 1 mg of Pd is presented in Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…The distribution of radionuclides between the solution and Pd precipitated from the desorbate formed in sorption recovery of palladium from true HLW [10] is presented in Table 4 as an example. The solution contained 690 mg l !1 Pd, 3 M HNO 3 and 0.1 M DTPA (the specific activity per 1 mg of Pd is presented in Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…23,24 Strong-base polyvinylpyridine resin not only demonstrates higher adsorption capacity of Pd(II) than resins with amino groups but also has good elution yield. 23 Further studies have revealed that weak-base polyvinylpyridine resin has stronger affinity for Pd than strong-base polyvinylpyridine resin and shows high adsorption selectivity because Pd can coordinate with lone pair electrons of nitrogen on pyridine. 24 It is expected that a combination of GO and pyridine groups will realize selective separation and recovery of Pd(II).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Pyridine and its derivatives are common functional groups on ion exchange resins which exhibit high performance for the recovery of Pd­(II). , Strong-base polyvinylpyridine resin not only demonstrates higher adsorption capacity of Pd­(II) than resins with amino groups but also has good elution yield . Further studies have revealed that weak-base polyvinylpyridine resin has stronger affinity for Pd than strong-base polyvinylpyridine resin and shows high adsorption selectivity because Pd can coordinate with lone pair electrons of nitrogen on pyridine .…”
Section: Introductionmentioning
confidence: 99%
“…Korolev et al . [ 38 ] compared two conventional macroporous anion exchangers, namely Dowex21 K and Amberlite IRA-900, with strong-base, macroporous vinylpyridine resin VP1-AP for the recovery of Pd from nitric acid medium. Zhang et al .…”
Section: Introductionmentioning
confidence: 99%
“…Liquid-core capsules with a non-cross-linked alginate fluid core surrounded by a gallon membrane were prepared in single step and investigated for the sorption of heavy metal ions [37]. Korolev et al [38] compared two conventional macroporous anion exchangers, namely Dowex21 K and Amberlite IRA-900, with strong-base, macroporous vinylpyridine resin VP1-AP for the recovery of Pd from nitric acid medium. Zhang et al [39] studied the recovery of palladium from simulated nuclear waste using a macroporous vinylpyridine anion-exchange resin embedded in porous silica beads and reported that the weak-base resin (SiPyR-N3) shows stronger affinity towards Pd(II) than a strong-base (SiPyR-N4) anion exchanger.…”
Section: Introductionmentioning
confidence: 99%